2018
DOI: 10.1056/nejme1808500
|View full text |Cite
|
Sign up to set email alerts
|

Finding Better Ways to Prevent Postpartum Hemorrhage

Abstract: Register to receive weekly email messages with the latest job openings that match your specialty, as well as preferred geographic region, practice setting, call schedule, and more. Visit the NEJM CareerCenter at nejmjobs.org for more information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…These RCTs found improved mortality when TXA was administered within 3 h of the start of bleeding due to trauma and PPH [117,118]. Ensuing publications have identified variance in these conclusions, and for this reason, these trials have become a source of controversy [5,8,11,15,111,[119][120][121][122][123][124][125][126][127][128][129][130][131][132]. However, it has also been suggested that fibrinolytic parameters of VHAs are not reliable for guiding the administration of TXA in PPH patients [73,109,110].…”
Section: Tranexamic Acidmentioning
confidence: 99%
“…These RCTs found improved mortality when TXA was administered within 3 h of the start of bleeding due to trauma and PPH [117,118]. Ensuing publications have identified variance in these conclusions, and for this reason, these trials have become a source of controversy [5,8,11,15,111,[119][120][121][122][123][124][125][126][127][128][129][130][131][132]. However, it has also been suggested that fibrinolytic parameters of VHAs are not reliable for guiding the administration of TXA in PPH patients [73,109,110].…”
Section: Tranexamic Acidmentioning
confidence: 99%
“…These large well-designed RCTs suggest that the utilization of TXA within 3 hours of bleeding, either from trauma or PPH, improved mortality. Subsequent studies have suggested that knowledge gaps in the CRASH-2 Trial and problems in defining PPH have made these trials a source of considerable and interesting discussion [7,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]. For the other prohemostatic agents, the utilization of soluble fibrinogen in Europe and cryoprecipitate in the United States is guided by VETs and Clauss fibrinogen [10].…”
Section: Platelet Functionmentioning
confidence: 99%
“…Since 1870s, peripartum hysterectomy has been performed to manage life-threatening postpartum haemorrhage (PPH) and uterine sepsis [1]. When bleeding cannot be controlled by conservative therapies, hysterectomy is performed as the definitive treatment and a life-saving procedure [2,3]. However, hysterectomy leads to the loss of fertility for women and can cause maternal morbidity and mortality [4].…”
Section: Introductionmentioning
confidence: 99%